THINKING ABOUT THE UNTHINKABLE: UNDERSTANDING APARTHEID VIOLENCE FROM THE PERSPECTIVE OF PROTAGONISTS - Palmary, Ingrid (PINS-Psychology in Society, 2025)
Foster, D, Haupt, P, and De Beer, M (2005) The theatre of violence: Narratives of protagonists in the South African conflict. Cape Town: HSRC Press. The theatre of violence offers a novel and insightful intervention into how we understand violence in the post apartheid era. It is novel because it deals with the largely neglected perspectives of perpetrators of violence, and insightful because it manages to balance the politics of such an attempt with a need for critical theoretical analysis. In researching (from a loosely narrative and discursive approach) protagonists in the apartheid violence, this book breaks new ground in carefully analysed ways that refuses simple answers.